Where Is East Asia in STS?. Issue 1 (1st March 2019) - Lin, Wen-yuan; Law, John
Abstract: The international spread of STS has reshaped the discipline in many ways, pushing it from its original core focus on technoscience in Euro-America to embrace new and wider agendas in other locations. For the practitioners of STS in East Asia, the complex relations between geographical region and forms of knowledge in technoscience are firmly on the agenda, and they have conceptualized these in a range of different and sometimes contradictory ways. The multiplicity of East Asian STS is also reflexively refracted in different assumptions about the character and location of the discipline in relation to other regional versions of STS. In what follows we simplify the complexities of a large and sophisticated body of writing by exploring a double question. On the one hand, we ask how scholars conceptualize the location of East Asian technoscience in the world. And on the other, a related question, we consider how they imagine the location of East Asian STS in relation to other forms of STS. We suggest that it is possible to identify at least six distinct spatially related strategies for understanding knowledge and technoscience in the East Asian literatures. In this article, we characterize these as diffusion, distortion, circulation, localizing, translation, and mistranslation and argue that East Asian STS may be understood as distinctive in the way it collaborates with other forms of STS not only because it identifies and characterizes other and different East Asian empirical contexts, but also because it makes possible the exploration of alternative and situated methodological approaches.